KEBIJAKAN STANDARISASI DATA DAN PROBLEM INTEROPERABILITAS PADA APLIKASI E-GO VERNMENT - Edhy Sutanta; Jazi Eko Istiyanto (CCIT Journal, 2012)
Interoperabilitybetween systemsine-Gov inlndonesiais animportantandurgentproblemtobe overcome. Data standardizationpolicyis an efforttowardsinteroperability, but itcanalsobe acause ofthe problemof interoperabilityine-Gov applications. Efforts tostandardizethe dataforthee-Gov systemhas beenperformedbyseverallocalandcentralgovernment agencies, butsince noclearframeworkof nationalguidelines, the majority ofdata standardizationis stillsectoral. This raises thenewproblemsrelated tointeroperabilitybefiveen systemsine-Gov. The neweffortis neededin the task ofdevelopa nationaldata standardsrequiredby allagencies sectors. Involvement ofallagenciesin the preparation ofnationaldata standardsnecessarytoanticipatethe variousneeds ofmulti-sectoraldata andinformation.Communication and InformationA/finistryof Indonesiais theappropriateagencytocarry outthe task,because it hassufficient authoritytothe horizontal(coordination function) and vertically(control function). This paperdiscusses thepolicy ofstandardization of dataandproblemsassociated with theinteroperabilityacross systemsine-Gov, and itsidea ofa solution to theproblem.